Partnerships do improve smallholder livestock systems: Experience from Limpopo and North West provinces in South Africa - Motiang, M.D.; Matjuda, L.E.; Nengovhela, B.N.; Clark, R. (TSAP and ILRI, 2006)
A profit thinking framework was used to select a multidisciplinary farmer support team (FST) to implement a focused participatory approach among livestock farmers in the Limpopo and North Western provinces of South Africa. Farmers were subsequently organised into teams, which meet once in 30 days to identify needs, set objectives, take actions with support from the FST and report every 90 days to measure progress. These meetings are also used to identify new opportunities for future actions. The results show that farmers recognise that profit maximisation should be the main focus of a beef enterprise with all other activities oriented towards this goal. Farmers were more eager to take actions that improved profit. Accessing new markets, learning pricing techniques and addressing issues such as transport costs, improved prices for beef. The FSTs obtained an indepth understanding of technical challenges in farmers’ operations and assisted farmers to implement appropriate solutions. The results showed that partnerships involving a dynamic mix of scientific knowledge and socio-economic conditions assist researchers and extension workers to considerably improve the performance of emerging beef farmers through participatory methods.